PENGARUH DISIPLIN DAN LINGKUNGAN KERJA FISIK TERHADAP KINERJA KARYAWAN PADA PT TEMPO MEDIA TBK JAKARTA SELATAN - Hudzaifah, Zahrah; Purnama, Aan (Journal of Research and Publication Innovation, 2024)
This research aims to determine The Influence of Discipline and Physical Work Environment on Employee Performance at PT Tempo Media Tbk, South Jakarta.This research uses quantitative methods with data collection techniques through distributing questionnaires and library/literature data. The population in this study was 300 employees. The sample used was 75 employees using the Slovin technique. Data analysis techniques use data instrument tests, classical assumption tests, simple linear regression, multiple linear regression, correlation coefficient, coefficient of determination. Hypothesis testing using the t test and F test. The results of the analysis show: discipline partially influences employee performance with a simple linear regression equation Y= 11.956+0.711 X1. The correlation coefficient value is 0.143, meaning it has a very low level of relationship and a coefficient of determination of 37.0%. meaning that performance is affected by 63.0%. This is proven by the t test, the calculated t value > t table (4.784 > 1.666) and reinforced by the significant value < 0.01 (00.00 < 0.01). The work environment partially has a positive effect on employee performance, shown by the simple linear regression equation Y= 17.290 + 0.585 This is proven by the t test, the calculated t value > t table (3.188 > 1.666) and reinforced by the significance value > 0.01 (0.002 > 0.01). The results of research on discipline and work environment simultaneously on employee performance are shown by the multiple linear regression equation Y = 9.580 + 0.485 X1 + 0.286 X2. The correlation coefficient value is 0.735, meaning it has a very strong level of relationship and the coefficient of determination is 59.7%, meaning performance is influenced by 61.0%. This is proven by the results of the F test hypothesis test, which shows that the calculated F value > F table (52.300 > 2.73) is confirmed by the significant value of 0.000 < 0.01. So the decision can be drawn that H0 is rejected and Ha is accepted.